Role of relative humidity, temperature, and water status in dormancy alleviation of sunflower seeds during dry after-ripening - Bazin, J. (2011)
The effect of various combinations of temperature and relative humidity on dormancy alleviation of sunflower seeds during dry after-ripening was investigated. The rate of dormancy alleviation depended on both temperature and embryo moisture content (MC). Below an embryo MC of 0.1 g H2O g-1 dw, dormancy release was faster at 15 °C than at higher temperatures. This suggests that dormancy release at low MC was associated with negative activation energy, supported by Arrhenius plots, and low Q10 values. At higher MC, the rate of dormancy alleviation increased with temperature, correlating well with the temperature dependence of biochemical processes. These findings suggests the involvement of two distinct cellular mechanisms in dormancy release; non-enzymatic below 0.1 g H2O g-1 dw and associated with active metabolism above this value. The effects of temperature on seed dormancy release above the threshold MC were analysed using a population-based thermal time approach and a model predicting the rate of dormancy alleviation is provided. Sunflower embryo dormancy release was effective at temperatures above 8 °C (the base temperature for after-ripening, TbAR, was 8.17 °C), and the higher the after-ripening temperature above this threshold value, the higher was the rate of dormancy loss. Thermodynamic analyses of water sorption isotherms revealed that dormancy release was associated with less bound water and increased molecular mobility within the embryonic axes but not the cotyledons. It is proposed that the changes in water binding properties result from oxidative processes and can, in turn, allow metabolic activities.